A multilevel model of the help-seeking behaviors among adolescents with mental health problems - Zhao, Mei; Hu, Mi (Frontiers in Integrative Neuroscience, 2022)
Objective: Mental health problems are highly prevalent among adolescents yet the utilization of mental health services among such a population is very low. This study was conducted to examine mental health problems and related help-seeking behaviors among a Chinese sample of adolescents. Methods A total of 3,480 students were recruited from four middle- and high schools in Changsha City, Hunan province, and completed an online questionnaire that assessed their general information, mental health problems including depression, anxiety, self-harm, and suicide ideation, as well as their help-seeking behaviors from both formal (including psychological teachers and mental health professionals) and informal sources (including family, friends, and teachers). Results The participants had a prevalence of 13.7% for depression, 11.5% for anxiety, 9.8% for self-harm, and 9.1% for suicide ideation. Although a high rate of help-seeking behaviors was observed (73.0%), most were concentrated in informal sources (99.3%), while only a small portion of participants resorted to formal sources (13.9%). Being female (OR: 1.45, 95% CI: 1.15–1.83), higher grade (OR: 1.32, 95% CI: 1.01–1.73), school mental health resources not available (OR: 1.39, 95% CI: 1.02–1.88), without suicide ideation (OR: 2.03, 95% CI: 1.42–2.90) were all associated with increased likelihood of formal help-seeking behaviors. On the other hand, complete middle school (OR: 0.36, 95% CI: 0.22–0.59), the middle level of academic ranking (OR: 0.64, 95% CI: 0.42–0.97), and higher father education levels (OR: 0.54–0.56, 95% CI: 0.33–0.90) were all associated with a decreased likelihood of formal help-seeking behaviors. Conclusion Our results showed a higher prevalence of help-seeking behavior for emotional or psychological problems during the past year. Compared to the high rate of informal help-seeking behaviors, students showed a lower propensity to seek formal help for their mental health problems, which may be explained by individual-level, family-level, and school-level factors. Our findings provide important implications for the development and popularization of targeted, needs-based mental health promotion and education programs in the future.